2000
DOI: 10.1034/j.1399-3003.2000.15b17.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 plasma levels are not elevated in patients with obstructive sleep apnoea

Abstract: Endothelin-1 (ET-1), a potent vasoconstrictor, is released mainly by vascular endothelial cells under the influence of hypoxia and other stimuli. ET-1 is related to endothelial dysfunction, as well as arterial and pulmonary hypertension, all of which are thought to be associated with obstructive sleep apnoea (OSA).This study evaluated venous plasma concentrations of ET-1 and noradrenaline and 24-h systemic blood pressure in 29 patients with OSA (age=56.9 1.6 yrs; body mass index=29.5 0.7 kg . m -2 (mean SEM)).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 28 publications
3
30
1
5
Order By: Relevance
“…The endothelium also produces vasoconstrictor substances, such as endothelin and angiotensin II, and levels have been reported as increased in OSAS and to fall with effective CPAP therapy [323]. However, other reports did not find an increase of endothelin in OSAS [324]. The Sleep Heart Health Study has also reported evidence of vascular dysfunction among older participants, particularly arterial diameter [325], identifying OSAS as an independent risk factor for impaired flow-mediated vasodilation.…”
Section: Endothelial Dysfunctionmentioning
confidence: 87%
“…The endothelium also produces vasoconstrictor substances, such as endothelin and angiotensin II, and levels have been reported as increased in OSAS and to fall with effective CPAP therapy [323]. However, other reports did not find an increase of endothelin in OSAS [324]. The Sleep Heart Health Study has also reported evidence of vascular dysfunction among older participants, particularly arterial diameter [325], identifying OSAS as an independent risk factor for impaired flow-mediated vasodilation.…”
Section: Endothelial Dysfunctionmentioning
confidence: 87%
“…However, the potential role of the confounding factors mentioned above was not specifically considered. On the other hand, ET-1, a potent vasoconstrictor produced by endothelial cells, has also been implicated in the pathogenesis of endothelial dysfunction and CV disease [27, 28], but studies in patients with OSAS have yielded conflicting results [29, 30]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this same study found that correction of sleep apnea reduced plasma endothelin to control levels. 8,9 However, Grimpen and coworkers 10 compared patients with obstructive sleep apnea with age-and weight-matched control subjects and found no differences in plasma levels of endothelin and no change in plasma endothelin after correction of the sleep apnea. Therefore, clinical studies do not provide a clear indication of the role of endothelin in sleep apnea-induced hypertension.…”
mentioning
confidence: 99%